The complete mitochondrial genome sequence of the hawk moth, Theretra oldenlandiae (Lepidoptera: Sphingidae) - Wang, Xu (Mitochondrial DNA B Resour, 2020)
In this study, we analyzed the complete mitochondrial genome sequence of the hawk moth, Theretra oldenlandiae. The complete mitogenome sequence of T. oldenlandiae was observed to be a circular molecule 15,312 bp long and consisting of 13 protein-coding genes (PCG), 2 ribosomal RNA (rRNA) genes, and 22 transfer RNA (tRNA) genes (GenBank accession number MN885801). The nucleotide composition is biased toward adenine and thymine (80.0% A + T). The A + T-rich region was found between rrnS and trnM, and this entire region was 423 bp long.